On Gulzar’s Poetry: Comparing the Three Versions of English Translation - Pallavi Kiran (University of Chitral Journal of Linguistics and Literature, 2025)
Gulzar’s merit as a contemporary Indian poet rests on his use of Hindustani, whichhas a high degree of emotional intensity, expressiveness, naturalness and unusualvividness that strikes the head and the heart of the listener. The study pragmaticallyand stylistically probes a randomly selected poem of Gulzar and its Englishtranslation by three translators, underlining, in the main, the variations in thelinguistic choices they make and the significant differences in their translation. Theanalysis discusses that which is complicated and complex in the poem; and how itis simplified by the translator, leaving out that which puzzles the poet. Thepragmatic-stylistic approach effectively identifies the translation shifts andinvestigates the value and belief system of Gulzar encoded in the language.